ISLAMIC FAMILY LAW AND GENDER PERSPECTIVE ON NOBLE AND LOWER CLASS MARRIAGES (CASE STUDY OF MANGKUNG VILLAGE, WEST PRAYE, CENTRAL LOMBOK) - Pratama, Muhammad Izziya; Musawar, Musawar (istinbath, 2025)
This research was conducted because, in the Merariq tradition, the Sasak tribe has a social hierarchy. Which, at every layer, influences Islamic Family Law and the Gender perspective. This research aims to analyze, from Islamic Family Law and perspectives, marriage among aristocratic and coralline descendants, with a research focus on case studies in Mangkung village, Central Lombok. Regarding gender equality and Islamic Law, different prices for Ajikrame occur when intermarriages occur between groups, especially those of noble descent and those of Jajarkarang descent. The incident of determining Ajikrame has a significant impact on marriage at the social level and affects Islamic Law, particularly in Islamic Family Law. Therefore, researchers are interested in exploring two research questions, namely (1) What is the practice of aristocratic and Jajarkarang marriages in Mangkung village, West Praya District, Central Lombok? (2) What is the Islamic Family Law perspective on noble and Jaja Karang marriages in Mangkung Village, West Praya District, Central Lombok? This research employs a qualitative approach with a descriptive type. The data collection method employed is a combination of documentation and interviews, while the data analysis method used is content analysis. The research utilizes both primary and secondary sources. The research results show that in the context of the marriage between Ningrat and Jajarkarang in Mangkung Village, West Praya District, Central Lombok, which was influenced by the determination of "Aji Krame," there are several aspects from the perspective of Islamic Family Law and Gender that can influence the social and cultural life of the local community. These aspects include societal alienation and its impact on gender justice. The practice of marriage between Ningrat and Jajarkarang in Mangkung Village, West Praya District, Central Lombok, is valid because it has fulfilled the conditions and requirements of a valid marriage transaction.